Adductor canal block versus continuous femoral nerve block in primary total knee arthroplasty: A meta-analysis. (July 2016) - Kuang, Ming-jie; Xu, Li-yan; Ma, Jian-xiong; Wang, Ying; Zhao, Jie; Lu, Bin; Ma, Xin-long
Abstract: Objective: Continuous femoral nerve block (CFNB) is considered the preferred analgesia after TKA. However, it may weaken quadriceps muscle strength, subsequently increasing the risk of falling. Adductor canal block (ACB) is a new sensory block technique that effectively relieves postoperative pain while preserving quadriceps strength. Thias meta-analysis was conducted to determine whether ACB of CFNB provides better pain relief and functional recovery after TKA. Method: The PubMed, Embase, Web of Science and Cochrane Library databases were comprehensively searched. Seven studies comparing ACB with CFNB in patients with TKA were enrolled in our meta-analysis. Review Manager 5.3 for Windows was used to analyse the extracted data. Results: Compared with the CFNB group, the ACB exhibited a significant decrease in visual analogue scale (VAS) score at rest within 24 h (p < 0.00001), as well as significant decreases in the length of hospital stay (P < 0.0001) and post-operative nausea (P = 0.03). ACB patients also exhibited greater improvements in ambulation ability (P = 0.01) and ambulation distance (P < 0.00001). There were no significant differences in the VAS score at rest 8 and 48 h following surgery, nor in the ambulation VAS score and opioid consumption two days following surgery. Conclusions: Compared with CFNB, ACB provides equally effective analgesia after TKA. ACB results in fast pain relief and early ambulation while decreasing post-operative nausea. ACB thus has the potential to replace CFNB as the gold standard for pain management in TKA patients. Highlights: We summarized the ACB analgesia effect after TKA and found that it can achieve fast pain relief and early ambulation. According to our study, ACB can alleviate postoperative pain as effective as continuous femoral nerve block. ACB therefore has the potential to replace CFNB as the gold standard in pain management for TKA patients.